Bahasa Inggris - Isyanty Khairunnisa; Heriyadi; Nur Afifah (Universitas Dr. Soetomo, 2024)
This research aims to examine the relationship between materialism and store atmosphere on compulsive buying where fashion interest is the mediating variable. The approach used in this research is quantitative research. This research is included in descriptive research with a survey method. The type of research used in this research is causal associative research. The population in this research is consumers of Kosshe Boutique Pontianak who have made purchases at least 2 times in the last 6 months and are female, with a sample of 200 respondents. Sampling in this research used a non-probability sampling method in the form of purposive sampling. The collected data was then analyzed using the Structural Equation Model with the SmartPLS statistical application tool version 3.9.3. The results of data analysis show that materialism has a significant effect on compulsive buying, store atmosphere has a significant effect on compulsive buying, materialism has a significant effect on fashion interest, store atmosphere has a significant effect on fashion interest and fashion interest is not significant on compulsive buying. The results of the mediation role test were not significant. Keywords : Materialism: Store Atmosphere; Fashion Interest; Compulsive Buying